Comparative Phytochemical Analyses of Resins of Boswellia Species (B. papyrifera (Del.) Hochst., B. neglecta S. Moore, and B. rivae Engl.) from Northwestern, Southern, and Southeastern Ethiopia - Bekana, D; Kebede, T.; Assefa, M.; Kassa, H. (Hindawi Limited, 2014)
Oleogum resins of B. papyrifera, B. neglecta, and B. rivae were collected from northwestern, southern, and southeastern Ethiopia, and their respective methanol extracts and essential oils were extracted and analyzed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). The investigation on essential oils led to the identification of 6, 7, and 8 constituents for B. papyrifera, B. neglecta, and B. rivae, respectively. The essential oil of B. papyrifera is mainly characterized by the presence of octyl acetate (57.1–65.7%) and n-octanol (3.4–8.8%). B. neglecta is rich in α-pinene (32.6–50.7%) followed by terpinen-4-ol (17.5–29.9%) and α-thujene (12.7–16.5%), whereas B. rivae was predominated by α-pinene (32.5–66.2%) followed by p-cymene (5.7–21.1%) and limonene (1.1–19.6%). Methanol extracts of the three Boswellia species were found to consist of diterpines (incensole, incensyl acetate and verticilla-4(20),7,11-triene), triterpenes (β-amyrin, α-amyrin, β-amyrenone, and α-amyrenone), nortriterpenes (24-noroleana-3,12-diene and 24-norursa-3,12-diene), and α-boswellic acid. The investigation on the methanol extract showed that only B. papyrifera contains diterpenes and nortriterpenes, whereas B. rivae and B. neglecta consist of only triterpenes. The results indicate that the three Boswellia species were characterized by some terpenes and these terpenoic constituents could be recognized as chemotaxonomical markers for each species.